Preparation and Evaluation of Liposomes and Niosomes Containing Total Ginsenosides for Anti-Photoaging Therapy - Jin, Yuanyuan; Liu, Da; Lu, Zhen; Yang, Lubing; Chen, Jiangli; Zhou, Xuyan; Qiu, Zhidong; Jin, Ye (Frontiers in Bioengineering and Biotechnology, 2022)
Ginsenosides are the principal bioactive compounds of ginseng. Total ginsenosides (GS) contain a variety of saponin monomers, which have potent anti-photoaging activity and improve the skin barrier function. To enhance the efficiency of GS transdermal absorption, GS liposomes (GSLs) and GS niosomes (GSNs) were formulated as delivery vehicles. Based on the clarified and optimized formulation process, GSL and GSN were prepared. The structure, cumulative transmittance, skin retention, total transmittance, and bioactivity of GSLs and GSNs were characterized. GSL and GSN were shown to inhibit lipid peroxidation and increase the contents of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) in human keratinocytes (HaCaTs). In addition, HaCAT cell migration, proliferation, and GS cellular uptake were significantly increased. The therapeutic effects of GSL and GSN were also evaluated in a rat model of photoaging. Histopathological changes were assessed in rat skin treated with GSL, GSN, or GS by hematoxylin–eosin (H&E) and aldehyde fuchsine staining. Malondialdehyde (MDA), SOD, GSH-Px, matrix metalloproteinases (MMPs), interleukin-6 (IL-6), interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α) expression levels were determined. Results indicated that the optimal formulation of GSL used soybean lecithin (SPC) as the phospholipid, with a lipid–drug ratio of 1:0.4 and a phospholipid–cholesterol ratio of 1:3.5. The optimal temperature for the preparation process of GSN by ethanol injection was 65°C, with a ratio of the organic phase to aqueous phase of 1:9. It was demonstrated that the cumulative release rate, skin retention rate, and total transmission rate of GSL-7 at 24 h were higher than those of GSN-4 and GS. GSL-7 significantly inhibited skin lipid peroxidation caused by ultraviolet (UV) radiation. In addition, GSL-7 reduced the contents of MMPs and inflammatory cytokines in skin tissue. In conclusion, GSL-7 may reduce skin aging caused by UV radiation and contribute to skin tissue repair.